2015
DOI: 10.1007/s10562-015-1544-1
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis of Coumarin Derivatives Using a SBA-15 Supported Cobalt(II) Nanocatalyst

Abstract: The catalytic performance of highly active cobalt(II) supported on mesoporous SBA-15 materials for the Pechmann reaction was investigated. SBA-15 supported cobalt(II) nanocatalyst was found to be efficient and easily recoverable in the Pechmann reaction of phenols and b-ketoesters to their corresponding coumarin derivatives under solvent-free conditions. The supported cobalt catalyst could be easily recovered after reaction completion and reused twelve times with an excellent durability and without any noticea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…Compared to previous reports [25,[42][43][44][45][46][52][53][54][55][56][57][58], this study also demonstrated that the surface area of the catalytic systems can be manipulated by the synthetic methodology. As can be observed from the obtained data, the acidic SiO 2 catalyst varies in the surface area in comparison to the one prepared from TEOS and displays more activity towards the Pechmann reaction.…”
Section: Methodsmentioning
confidence: 41%
See 1 more Smart Citation
“…Compared to previous reports [25,[42][43][44][45][46][52][53][54][55][56][57][58], this study also demonstrated that the surface area of the catalytic systems can be manipulated by the synthetic methodology. As can be observed from the obtained data, the acidic SiO 2 catalyst varies in the surface area in comparison to the one prepared from TEOS and displays more activity towards the Pechmann reaction.…”
Section: Methodsmentioning
confidence: 41%
“…Even though there are several studies addressing the catalytic performance of a variety of heterogeneous solid catalysts in producing coumarin compounds via Pechmann condensation, most of these methodologies suffer from some drawbacks such as long reaction time, swelling tendency, low surface area, stability of the catalysts and their costs [51][52][53][54][55][56][57]. In order to overcome some of these obstacles and as a continuation to our research in developing a new and efficient catalytic protocol for the effective synthesis of coumarins, this report elucidates the synthesis of three new catalytic systems of sulphated and phosphated nanoparticle of silica, titania and silica prepared from TEOS catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…As clearly shown in Table 2, catalytic activity of MNESA depended on both phenol and bketoester substrates, and all phenols were rapidly converted to the corresponding products in good to excellent yields. A plausible mechanism of Pechmann condensation reactions for the synthesis of coumarins between b-ketoester compounds and phenols has been proposed according to literature (Scheme 3) [15][16][17][18][19][20][21]. At first, esterification reaction of phenol 1 and b-ketoester compound 2 in the presence of catalyst lead to intermediate 4.…”
Section: Pechmann Condensation Using Mnesa Catalystmentioning
confidence: 99%
“…Although various methods have been reported for this reaction, they suffer from disadvantages such as long reaction time, using expensive and/or nonstable catalyst and using heterogeneous catalysts [15][16][17][18][19][20][21]. There is widespread interest in the synthesis of new coumarin derivatives, because of their applications in organic synthesis, biology, medicine, perfumes and cosmetics fields [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…These include a good reusability coupled with high activities and specificities in different chemistries based on their excelling properties (high surface areas, degenerated density of energy states and plasmon) [52][53][54]. In this regard, Co/supported catalysts were previously reported to be highly active and versatile for acid and redox catalyzed processes [54,55].…”
Section: Introductionmentioning
confidence: 99%